O IPTU progressivo e sua função social: análise da implantação desse instrumento na cidade de Palmas – TO - Cruz, João Carlos Lima (Universidade Federal do Tocantins, 2017)
Palmas, the newest planned capital of a brazilian state, in spite of the short time that has elapsed since its genesis, presents, like so many other cities of our country, elements related to real estate speculation who lead not only to the disordered occupation of its urban spaces, but also to the socio-territorial exclusion and to the urban deconsolidation due to the several empty spaces. These problems are the result of a housing market characterized by the economic aspect to the detriment of the social. In order to solve, or at least minimize, the causes of this complex process, the extra-fiscal instrument was instituted - the time-progressive IPTU, with the objective that the urban property could fulfill its social function. This fact justified the present study, since it is necessary to reflect upon the current situation of this tax that, after 8 years of its institution, does not seem to have contribute to solve these problems. In order to analyze the reasons for such difficulties, we analyzed the variation in the values of the real estate circumscribed in the areas subject to Parcelamento, Edificação e Utilização Compulsórios - PEUC (Compulsory Installment, Building and Use), where it was concluded that the progressivity of the tax has the capacity to trigger a process of control of the Real estate market fostering the social function of urban property. However, the instrumentalization in the applicability of the legislation implemented by the Municipal Public Power, due to tax evasion, can result in the absence of the application of the expropriation sanction, which causes obstacles to the implementation of the social function of urban property